Cellular growth in plants requires regulation of cell wall biochemistry. (February 2017) - Chebli, Youssef; Geitmann, Anja
Abstract : Cell and organ morphogenesis in plants are regulated by the chemical structure and mechanical properties of the extracellular matrix, the cell wall. The two primary load bearing components in the plant cell wall, the pectin matrix and the cellulose/xyloglucan network, are constantly remodelled to generate the morphological changes required during plant development. This remodelling is regulated by a plethora of loosening and stiffening agents such as pectin methyl-esterases, calcium ions, expansins, and glucanases. The tight spatio-temporal regulation of the activities of these agents is a sine qua non condition for proper morphogenesis at cell and tissue levels. The pectin matrix and the cellulose-xyloglucan network operate in concert and their behaviour is mutually dependent on their chemical, structural and mechanical modifications.